Shortorn cattle of West and central Africa III. Physical, adaptive and special genetic characteristics - Aboagye, G.S.=700 1 Tawah, C.L.; Rege, J.E.O.
(Fr, Es)
Ilus., ref.
Keywords: GANADERIA; VARIACION GENETICA; ADAPTACION; PRODUCCION ANIMAL; AFRICA CENTRAL; VACUNOS SHORTHORN; REVISTA MUNDIAL DE ZOOTECNIA